SPIRITUAL ASSESSMENT AND SYMPTOM DISTRESS AMONG CANCER PATIENTS - Ghani, Nasreen; Suliman, Muhammad; Ghani, Shaheen; Yaseen, Muhammad (Annals of Allied Health Sciences, 2020)
OBJECTIVE: To find out the spiritual assessment and physical symptoms distress or discomfort among cancer patients and also to determine any possible association between these two variables in the same subjects. METHODS: Descriptive cross-sectional study of 168 cancer patients taken from the IRNUM Hospital Peshawar and responses recorded with validated and reliable questionnaires of FACIT-SP and SDS scales. RESULTS: Women accounts for 53.6% and the median age of the total participants were 43 years. The participants’ mean score on the FACIT-SP scale was 42.80, and on SDS scale was 26.88. The negative statistical correlations among the two variables; functional assessment of chronic illness therapy-spiritual well-being (FACIT-SP) and symptom distress scale (SDS) on Pearson correlation (r) was significant and inversely associated (r = 0.619, p < 0.000). CONCLUSION: The results of this study is similar with that of the other many studies in which support of the hypothesis that spirituality is a predictor and mediator positively associated with the positive outcomes like quality of life, hope, meaning, purpose and satisfaction in life and negatively or inversely associated with negative outcomes of life like physical discomfort and physical distress etc. The study suggests strengthening spiritual diversifications in a disease status for the better health outcomes and construction of a healthy lifestyle.